Statistical Analysis on Factors Associated with Job Satisfaction of Teachers among Secondary Schools in Bidur Municipality, Nuwakot, Nepal - Lamichhane, Krishna Ram; Banjade, Ishwari Prasad (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Job satisfaction among secondary school teachers plays a vital role in fostering the quality of education and ensuring teacher retention. Identifying the factor influencing their job satisfaction can help policymaker and relevant authorities to build supportive and positive work environment. This study sought to identify key demographic, socioeconomic and job-related factors associated with secondary level teachers job satisfaction. Method: A cross-sectional study was conducted using self-administered questionnaire among 381 teachers from 17 private and 21 government school. Statistical analyses, including bivariate analyses were used to examine the relationship between job satisfaction and various factors, followed multivariate analysis using ordinal logistic regression. The model was fitted after confirming it satisfied diagnostic test for multicollinearity, proportional odds assumption and goodness of fit. Result: The distribution of job satisfaction among secondary school teachers were as follows: dissatisfied (14.2%), neutral (34.1%), and satisfied (51.7%). Bivariate analysis showed no significant association between job satisfaction and demographic factors such as age, gender, ethnicity, monthly salary, marital status, teaching years, school type (p>0.05). However, family satisfaction, school location and job-related factors showed significant association with job satisfaction (p ≤ 0.05). The ordinal logistic regression model identified seven major predictor of job satisfaction: working condition, pay, responsibility, job security, recognition, workload, and local government support. Conclusion: The study concludes that job satisfaction among secondary school teachers is influenced more by job-related factor than by demographic and socioeconomic characteristics. Critical aspect such as working condition, pay structure, job security, responsibility, recognition, manageable workload, and support from local government should be given priority by educational policymaker and school authorities to enhance teacher satisfaction and overall quality of education.